Exploration and formulation of an appropriate environment education approach for early childhood learners - Lestiawati, I Made; Hartati, Sofia; Sumantri, Mohamad Syarif (Edelweiss Applied Science and Technology, 2025)
This study aims to explore and develop an effective environmental care learning approach for early childhood to achieve maximum results. It employs a literature study method, specifically an integrative literature review. The study is conducted in four stages: designing the review, conducting the review, analyzing the data, and writing the review. Data were collected from scientific journals that are accredited or indexed nationally and internationally. The data collection was conducted online using the Publish or Perish application with several keywords related to the research objectives. The gathered data were analyzed using content analysis. The results indicate that the learning strategy employed in environmental education must meet several criteria, including a holistic approach, empowerment through age-appropriate activities, education through play and stories, daily experiences, family and community-based socialization, and evaluation of engaging content. Regarding learning media, it should also meet several criteria such as interactivity, visual appeal, exploratory activities, repetition, technology use, and cultural relevance. Furthermore, to evaluate environmental education, the aspects to consider include students’ knowledge, attitudes, and behavior, experimental methods, social and environmental context, parental involvement, connection with nature, psychological well-being, and both short-term and long-term impacts. The findings of this study provide valuable contributions to implementing environmental education for early childhood by guiding the execution of effective environmental education strategies.